Prosedur dan Fungsi Administrasi Pendidikan Pada Yayasan Pendidikan Al-Hikmah - Aurin, Nasyah; N, Nurjannah; Wahidha, Tasya Agustina; Astuti, Widia (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Educational administration is a collaborative process that aims to achieve educational goals by examining the relationships between educational components so that the educational system can be improved by using tools that support its activities. Administrative procedures are a sequence of steps taken to carry out administrative activities. Educational administration procedures are a sequence of steps taken to carry out administrative activities in an educational institution such as a school. In this article the author examines the urgency of educational administration in a school, who is involved in educational administration, how educational administration procedures provide benefits to the school, and what factors become obstacles in the management of educational administration as well as the object of study and targets of administration education in school. The method used is a descriptive method through research research and literature review by collecting references and information related to the problem being studied. In general, educational administration procedures and functions must be carried out sequentially in order to obtain good and effective results. Procedures are very important as part of the implementation of an activity to achieve the goals or objectives to be achieved. Without procedures and educational administration functions, an institution such as education cannot achieve its goals. Therefore, administrators participate so that educational administration achieves its goals. Educational administration procedures require various approaches to achieve goals, one approach is an integrated approach.